Leitura, linguagem e letramento: o conto de fadas no ensino fundamental - Mourão, Mônica Assunção (Universidade do Vale do Rio dos Sinos, 2015)
This present study aimed to identify how the literary literacy of the students of the early elementary school occurs. For this the research was carried out in a class of 5th year of a public municipal school in Imperatriz, Maranhão. In the theoretical foundation was indispensable the theoretical conception of authors such as Vygotsky (1988), Bakhtin (1995, 1997), Bettelheim (2002), Bronckart (2006), Schneuwly and Dolz (2004), Soares (2004, 2009, 2011), Rojo (2008) , Guimarães and Kersch (2012), Marcuschi (2008), Cosson (2012), and Mota-Roth (2011) among others, as they bring to the center of the current discussions the role of the Applied Linguistics in relation to the understanding we have about genres and literacy. The basis of this study is just up the process entitled, at the time of the 80’s, such as literacy, so, a directed look not only to the reading and writing acquisition, but also to the development of the individual as a social being, inserted in a literacy society which makes use of the language in different contexts, with innumerous purposes and specific objectives. The research is configured with the interpretative qualitative aspects of the action and, beyond the observation, it was taken as the instruments the semi-structured interview and the dairy field. The data revealed that there was the literary literacy even though was not enough in the classroom. Thus, it can be said that the literary literacy can occurs since the early years of schooling, despite of the obstacles that mainly the peripheral schools face. It was also realized that, if the work with the literary text is more dynamic and systematic, the results achieved can be quite significant to the process of development of writing and reading. The literary literacy workshop applied by the researcher gave rise to such claim, because the interest of the class was always something present during the classes of Portuguese, Literature and Textual Production, but it takes a greater number of them to move forward on this issue.
Keywords: Letramento; Letramento literário; Gênero textual; Conto de fadas; Literacy; Literary literacy; Genres; Fairy tales; ACCNPQ::Lingüística, Letras e Artes::Lingüística